Protection from Anti-Free Speech Persuasion: An Experimental Testing of Inoculation Strategy in Building Resistance to Persuasive Anti-Free Speech Messages among Filipino Youth - Cruz, Karl Lewis L. (Philippine Humanities Review; Vol 25 No 1: Philippine Humanities Review (2023-2024): Rebyu ng Arte at Literatura ng Pilipinas, 2025)
With the arguments against free speech birthed by the long-standing political conditions in the Philippines, and the influence strategies including appeals to logic and emotions demonstrated by such anti-free speech messages — the right and value for free speech among the Filipinos appear to face significant threats. Communication scholars and social psychologists alike argue that we now have a crucial need for psychological resistance against various forms of harmful persuasion including anti-free speech persuasion. As a response, this article sought to contribute to the protection of positive beliefs in and values for free speech by testing the effectiveness of inoculation strategy and its two components — threat and refutational preemption — in building resistance to anti-free speech persuasion. Inoculation strategy, as operationalized here, is a belief and attitude protection strategy derived from the principles of William McGuire’s inoculation theory. This factorial quasi-experimental research differentiated the effects of various inoculation treatments in inducing resistance among 162 Filipino high school students to simulated anti-free speech messages. Three experimental conditions — full inoculation, threat inoculation, and refutational inoculation — were tested against a control condition where no inoculation treatment was provided to the participants. Results showed that full inoculation, a treatment where both components of the strategy were provided, induced the greatest persuasion resistance and led to the smallest attitude change in the face of anti-free speech persuasion. Threat inoculation, wherein only the threat component was provided, was also found to be effective. The findings of this article further support the possibility of utilizing inoculation strategy in protecting our value for freedom of speech and democracy from anti-free speech persuasion in both global and local contexts.